Multimodality imaging can shift the clinical approach and prognosis of a patient: from heart failure and angina to cardiac amyloidosis - Alexandra Maria Chitroceanu; Alina Ioana Nicula; Roxana Cristina Rimbas; Mihaela Andreescu; Cristina Popp; Claudiu Stoicescu; Dragos Vinereanu (Sciendo, 2021)
AL (light chain) amyloidosis is a life threatening disease. Untreated patients with involvement of the heart, a condition known as cardiac amyloidosis (CA), tend to have the most rapid disease progression and worst prognosis. Therefore, it is essential to early recognize the signs of symptoms of CA, and to identify the affected individuals with readily available non-invasive tests, as timely therapy can prolong life. Different imaging tests are used to diagnose and stratify the risk of the disease noninvasively, and to follow-up of the disease course and response to therapy. In this light, we present a case of a woman with cardiovascular risk factors, initially admitted for typical angina and decompensated heart failure (HF), who was later diagnosed with AL amyloidosis with cardiac involvement, by using multimodality imaging assessment in a step-by-step fashion. This changed completely the prognosis of the patient. Timely chemotherapy and stem cell transplantation led to an improvement in clinical status, biomarkers, and in a regression of amyloid myocardial infiltration showed by imaging.